COMBINING ABILITY ANALYSIS FOR YIELD AND YIELD COMPONENT CHARACTERS IN RICE (Oryza sativa L.) - D. SRINIVASA CHARY, Y. ANUSHA, L. KRISHNA, K V. RADHAKRISHNA and (The Journal of Research, PJTSAU, 2019)
Rice (Oryza sativa) is one of the major staple food crop being grown worldwide. It is the staple food for more than half of the world’s population. It is a nutritious cereal crop, provides 20 per cent of the calories and 15 per cent of protein consumed by world’s population. Besides being the chief source of carbohydrate and protein in Asia, it also provides minerals and fibre.